THE IMPORTANCE OF HISTORICAL AND MODERN SOURCES IN TEACHING THE LIFE AND WORK OF ALISHER NAVOI - Ishonkhanova Iroda Abduvakhitovna (Journals Park Publishing, 2024)
The teaching of Uzbek classical literature in the general secondary education system is one of the most important and urgent issues today. The article discusses the effective use of sources in the study of Alisher Navoi's life and work.
Keywords: general secondary education system, life and work of Alisher Navoi, historical source, modern source